Evolution of the hyperparameter t in relation to the LR and MLP models. - Roberta Moreira Wichmann (14259316) (2025)
This figure illustrates the convergence of the AUC-ROC metric across iterations of the hyperparameter t for the Logistic Regression (LR) and Multilayer Perceptron (MLP) models in the federated learning framework. The graph demonstrates how the predictive performance stabilizes as t increases, with significant convergence observed around 5 iterations. This analysis highlights the importance of hyperparameter tuning to balance model performance and computational efficiency in federated learning. This figure was developed by the authors. (TIFF)